El ritmo estacional en los fenómenos cíclicos endocrino-sexuales de la rana criolla (Leptodactylus ocellatus (L) del Norte argentino - Cei, José Miguel Alfredo María (1949)
In both sexes of Leptodactylus ocellatus (L.) there is a marked correspondence between the periodic reproductive activity and the climatic conditions of the natural enviroment. Rain is the dominant factor in the annual rhythm of the cycle. The ovarie cycle of the 9 in the Tucuman region involves : an autumn-winter period of atresia of the ovocytes not expelled the preceding year and of progressive and intense auxocytic and vitelligenous activity ; and a spring-summer period of rut and deposition, with masses of mature eggs, a few ovocytes in their first stages of development and be-' ginning of the reabsortion of the ovocytes not expelled (February-March).’ The oviducts develop between September and April (acme in December-. January) and degenerate between April and June, with a minimum of. development in July. The spermatogenetic cycle of the cP has long period of lack of regenerative activity in summer (December-April) ; testes with protogonia and bundles of spermatozoids. The reactivation begins in April but proceeds with anormal and scanty activity (abundance of degenerative forms) in. the rathêr cold months at the end of autumn and winter. In September the hibernal degenerative forms are almost entirely expelled and it is followed by a strong synchronic regenerative period, the new big spermatogenetic « poussée » ends practically at the very end of October with the formation of new bundles very soon detached to be used in the period of spring rut. During the end of October, in November and also during the first days of December, the spermatogenesis automatically ends (probably due to the lack of gonadotropic follicle stimulant secretion) and large degenerative forms of spermatogonia and spermatocytes can be observed in the testes. There is one period (October and November) in which spermatogenesis and rut overlap. The male C.s.s. 1 have been enumerated and decribed in this paper, and their annual development reaches its maximum between October and March. The dark pigmentation of the thorns of the thumbs is not very sensitive to the psycho-hypophysarian reflexes of the cautivity shock wich likewise appear seasonally in animals that have been kept for months in the laboratory. Under experimental conditions an optimal temperature can accelerate in two months during winter time the spermatogenic process in the majority of the examined specimens hindering in that way the production of many nocive cellular degenerative forms acting also perfect darkness. There are in Corrientes (laguna de Manantiales, Paraná) two forms of this species morphologically different referred in this paper as reticulata and typica which presented during the months of October, November and December 1948: those of reticulata spermatogenesis of the continuous type (Cf. Discoglossus pictus) without summer interruption of the gametogenetic activity and without terminal degenerations ; those of typica spermatogenesis with seasonal interruption of the gametogenetic activity, similar to the one observed in the forms of Tucumán and Chaco. Some hypothesis upon the possible genetic and phylogenetic relationship between both forms are discussed.